ANALISIS SISTEM PENGENDALIAN MANAJEMEN TERHADAP KINERJA MENGELOLA & MENGATUR PERSEDIAAN DI GUDANG PT. XYZ TBK. SUMEDANG - Resmiati, Novia (COMPETITIVE, 2023)
AbstractAnalysis of management control system on the performance of inventory in the warehouse of PT. XYZ Sumedang is an observational activity in order to present information on how manage the warehouse of PT. XYZ conducted in the Sumedang area as the second distributor after the Bandung branch The method used is by observation, and literature study, which supports the completion of the elements of the management control system. Based on the result of analysis carried out, it can be concluded that procedures for distribution of goods at PT. XYZ is clear and can be said to be good and in accordance with company regulations. The company already has a Standard Operational Procedure and application of management control system for distribution of goods PT. XYZ has been running well and effectively, because it has fulfilled the elements of the management control system. Key words: distribution, inventory, management control system